2012
DOI: 10.1186/1471-2229-12-130
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the grapevine stilbene synthase multigenic family: genomic organization and expression profiles upon biotic and abiotic stresses

Abstract: BackgroundPlant stilbenes are a small group of phenylpropanoids, which have been detected in at least 72 unrelated plant species and accumulate in response to biotic and abiotic stresses such as infection, wounding, UV-C exposure and treatment with chemicals. Stilbenes are formed via the phenylalanine/polymalonate-route, the last step of which is catalyzed by the enzyme stilbene synthase (STS), a type III polyketide synthase (PKS). Stilbene synthases are closely related to chalcone synthases (CHS), the key enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
278
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(302 citation statements)
references
References 104 publications
14
278
1
1
Order By: Relevance
“…The available literature data demonstrate that STS genes in sorghum, spruce, pine, peanut, and mulberry form small gene families composed of 1-10 members (Preisig-Müller et al 1999;Yu et al 2005;Paterson et al 2009;Zhu et al 2014;Warren et al 2015;Li et al 2016), while STS gene family in grapevine consists of 48 STS genes with at least 32 potentially functional ones as revealed by the genomewide analysis of the grapevine genome (Vannozzi et al 2012;Parage et al 2012). Functional analysis of nine STS genes representing most diversity of the STS gene family in grapevine performed by Parage et al (2012) revealed that the genes encode proteins possessing STS activity.…”
Section: Stilbene Biosynthesismentioning
confidence: 99%
See 3 more Smart Citations
“…The available literature data demonstrate that STS genes in sorghum, spruce, pine, peanut, and mulberry form small gene families composed of 1-10 members (Preisig-Müller et al 1999;Yu et al 2005;Paterson et al 2009;Zhu et al 2014;Warren et al 2015;Li et al 2016), while STS gene family in grapevine consists of 48 STS genes with at least 32 potentially functional ones as revealed by the genomewide analysis of the grapevine genome (Vannozzi et al 2012;Parage et al 2012). Functional analysis of nine STS genes representing most diversity of the STS gene family in grapevine performed by Parage et al (2012) revealed that the genes encode proteins possessing STS activity.…”
Section: Stilbene Biosynthesismentioning
confidence: 99%
“…However, there are currently no clear experimental data whether grapevine and other plant STS proteins in each multigene family differ in their enzyme activities and specificity for stilbene biosynthesis. The expressional analyses of the STS gene family members in grapevine and mulberry revealed that some STS genes exhibit differences in transcriptional responses during development and in response to environmental stresses (Vannozzi et al 2012;Shi et al 2014;Dai et al 2012). There were also differences in tissue-specific expression of some grapevine and mulberry STS gene family members (Vannozzi et al 2012;Shi et al 2014;Li et al 2016).…”
Section: Stilbene Biosynthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Resveratrol is synthesized by a one-step reaction (Hanhineva et al, 2009) of resveratrol synthase gene (RS) that is differentially regulated under different stimuli and in different tissues (Chung et al, 2003) and belongs to a large multigene family (Vannozzi et al, 2012). Arachis hypogaea RS genes were already cloned (Schröder et al, 1988;Huang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%